2022
DOI: 10.1002/ijc.33947
|View full text |Cite
|
Sign up to set email alerts
|

Cancer‐associated fibroblasts at the unfavorable desmoplastic stroma promote colorectal cancer aggressiveness: Potential role of ADAM9

Abstract: The tumor microenvironment plays a key role in cancer aggressiveness.Desmoplastic reaction (DR), morphologically classified as Mature, Intermediate and Immature types, has previously been shown to be highly prognostic in colorectal cancer (CRC) and it consists to a large extent of cancer-associated fibroblasts (CAFs). The aim of our study was to characterize the molecular background of DR and understand the effects of CAFs in tumor aggressiveness. The prognostic significance of DR was initially examined in 149… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…[18,19] For example, CAFs secrete ADAM9 to stimulate the growth and migration of human CRC cells. [20] Our study, based on bulk RNA sequencing and scRNA sequencing data, validated that more CAFs were enriched in the tumor microenvironment compared to the adjacent normal microenvironment. Besides, in line with the previous finding, [10] we uncovered that there were 3 subtypes of CAFs in CRC tissues.…”
Section: Discussionmentioning
confidence: 67%
“…[18,19] For example, CAFs secrete ADAM9 to stimulate the growth and migration of human CRC cells. [20] Our study, based on bulk RNA sequencing and scRNA sequencing data, validated that more CAFs were enriched in the tumor microenvironment compared to the adjacent normal microenvironment. Besides, in line with the previous finding, [10] we uncovered that there were 3 subtypes of CAFs in CRC tissues.…”
Section: Discussionmentioning
confidence: 67%
“…Ao and colleagues demonstrated that CAFs derived from colorectal cancer tissue with immature-type DR overexpressed ADAM9s and stimulated cell proliferation and migration of colorectal cancer cell lines in vitro . In this regard, they supposed ADAM9-targeting antibody–drug conjugates may be a good drug candidate ( 29 ). However, predictive value of DR on ACT has been rarely reported in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to ECM stiffness and further feedback to TGF-β induction and contributes to a tumor-promoting inflammatory environment [33,34]. CAFs also secrete a disintegrin and metalloproteinase 9 (ADAM9), which has been implicated in increasing the proliferation and dissemination of CRC cells [35]. Recent literature suggests that ADAMs are considered biochemical markers of GI tumorigenesis due to their protein hydrolysis and adhesion activities [36,37].…”
Section: Caf-mediated Ecm Remodeling In Tumor Progressionmentioning
confidence: 99%